(untitled) (Bangladesh Journal of Urology, 2025)
Background: Transurethral resection of the bladder tumour located in the lateral wall, postero-lateral wall and lateral aspect of bladder neck under spinal anaesthesia is often hampered by obturator jerk, which may cause serious complications like bladder perforation. Using obturator nerve block along with spinal anaesthesia can overcome this problem. There are various techniques of obturator nerve block. Classic approach is most commonly used technique for obturator nerve block. It effectiveness can be increased by using a nerve stimulator to locate the nerve precisely. Also a transvesical approach using a cystoscope is reported to be effective. Objective: To compare the effectiveness of obturator nerve block between classic approach using a nerve stimulator and transvesical approach in terms of elimination of obturator jerk. Materials and Methods: This study was conducted in the Department of Urology, Bangabandhu Sheikh Mujib Medical University, Shahbag, Dhaka from May 2018 to August 2019. Total 81 patients underwent transurethral resection of bladder tumour (TURBT) under spinal anesthesia for bladder tumour located at the lateral wall, postero-lateral wall and lateral aspect of bladder neck. They were divided into two groups by randomization. 42 patients in group I received obturator nerve block (ONB) by classic approach using a nerve stimulator and 39 patients in group II received ONB by transvesical approach. The effectiveness of both techniques were observed in terms of the elimination of obturator jerk, ability of the surgeon to completely resect the tumour, and presence of detrusor muscle in the histopathological specimen. Results: Complete elimination of obturator jerk was significantly higher in group I (100% vs. 79.5%; P = 0.002). In terms of ability to completely resect the visible tumour, effectiveness of both techniques were similar (100% vs. 97.4%; P = 0.481). The presence of detrusor muscle in the histopathological specimen was significantly higher in group I (90.5% vs. 64.1 %; P = 0.007). Bleeding requiring transfusion was low and similar in both groups (7.1% vs. 10.3%; P = 0.707). No bladder perforation occurred or systemic effect of lignocaine injection was observed. Conclusion: Compared to transvesical approach, the classic approach with a nerve stimulator was more effective for obturator nerve block and presence of detrusor muscle in the histopathological specimen. In terms of surgeon’s ability to completely resect the visible tumour, effectiveness of both techniques were similar. Bangladesh J. Urol. 2024; 27(1): 48-54